Rusalka - Kvapil, Jaroslav (Modern Czech Classics Ser., 2020)
Famous as the libretto for Antonín Dvorák's opera of the same name, Jaroslav Kvapil's poem Rusalka is an intriguing work of literature on its own. Directly inspired by Hans Christian Andersen's famous "The Little Mermaid," Kvapil's reinterpretation adds an array of nuanced poetic techniques, a more dramatic tempo, and dark undertones that echo the work of eminent Czech folklorist Karel Jaromír Erben. All of these influences work in tandem to create a poetic work that is familiar yet innovative.Transposed into the folkloric topos of a landlocked Bohemia, the mermaid is rendered here as a Slavic rusalka--a dangerous water nymph--who must choose between love and immortality. Thus, Rusalka, while certainly paying homage to the original story's Scandinavian roots, is still a distinct work of modern Czech literature. Newly translated by Patrick Corness, Kvapil's work will now find a fresh group of readers looking to get lost in one of Europe's great lyrical fairy tale traditions.